2003
DOI: 10.1002/ptr.1167
|View full text |Cite
|
Sign up to set email alerts
|

Screening of 25 compounds isolated from Phyllanthus species for anti‐human hepatitis B virus in vitro

Abstract: Using an HBV-producing cell line and inhibition of the expression of the HBsAg and HBeAg as antiviral indicators, a study was conducted on 25 compounds isolated from four Phyllanthus (Euphorbiaceae) plants, including P. amarus Schum. & Thonn., P. multi florus Willd., P. tenellus Roxb. and P. virgatus Forst. f. It was found that niranthin (1), nirtetralin (3), hinokinin (5) and geraniin (13) at the non-cytotoxic concentration of 50 micro m, suppressed effectively both HBsAg and HBeAg expression, with the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 15 publications
1
67
1
4
Order By: Relevance
“…Phyltetralin, nirtetralin and niranthin exhibited anti-inflammatory activity by inhibiting carrageenan-induced paw oedema and neutrophil influx (Kassuya et al 2005). Huang et al (2003) reported the anti-HBsAg and anti-HBeAg activities of niranthin and nirtetralin and the compounds suppressed HBsAg and HBeAg expression effectively at a non-cytotoxic concentration of 50 mM.…”
Section: Lignansmentioning
confidence: 99%
“…Phyltetralin, nirtetralin and niranthin exhibited anti-inflammatory activity by inhibiting carrageenan-induced paw oedema and neutrophil influx (Kassuya et al 2005). Huang et al (2003) reported the anti-HBsAg and anti-HBeAg activities of niranthin and nirtetralin and the compounds suppressed HBsAg and HBeAg expression effectively at a non-cytotoxic concentration of 50 mM.…”
Section: Lignansmentioning
confidence: 99%
“…Thus, the application of light qualities in tissue cultures could be a useful strategy for improving therapeutic metabolites under standardized conditions, and it is certainly useful in plantlet production. In our study, we showed that yellow light stimulated the production of phenolic compounds that are the main therapeutic constituents of P. tenellus, including tannins and flavonoids (Huang et al, 2003), suggesting that yellow light plays an important role in the biosynthesis of phenolic compounds in P. tenellus. The use of HPLC coupled to a diode array detector revealed a higher amount of phenolic compounds in crude aqueous extracts.…”
Section: Discussionmentioning
confidence: 56%
“…In particular, this species, also known as quebra-pedra or ervapombinha, is used in folk medicine to treat kidney disease, urinary bladder disturbances and hepatitis (Lorenzi and Matos, 2008). The therapeutic value of P. tenellus arises from its phenolic compounds, including tannins and flavonoids (Huang et al, 2003). Environmental, physical and biotic factors all interact to affect plant development, resulting in morpho-anatomical and physiological phenotypic plasticity (Catoni et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to exhibit marked anti-hepatitis B virus surface antigen activity both in in vivo [1][2][3] and in vitro studies [4,5]. Furthermore, the plant has been reported to possess antibacterial [6], anticrustacean [7], antiviral [8], anti-inflammatory [9], anticancerous [10], antidiabetic, and anticholesterol activities [11]. Different parts of plant are ethnobotanically reported to have various therapeutic activities such as expectorant, diaphoretic, and diuretic [12].…”
Section: Introductionmentioning
confidence: 99%